2017
DOI: 10.4236/ajps.2017.86083
|View full text |Cite
|
Sign up to set email alerts
|

Maize Development: Cell Wall Changes in Leaves and Sheaths

Abstract: Developmental changes occur in maize (Zea mays L.) as it transitions from juvenile stages to the mature plant. Changes also occur as newly formed cells mature into adult cells. Maize leaf blades including the midribs and sheaths undergo cell wall changes as cells transition to fully mature cell types. As is common in grasses during cell wall maturation, the lignin in the plant tissue is acylated with p-coumarates (pCA). This work characterizes cell walls in maize that make up leaf blade, leaf midrib, and sheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Ground samples were processed following the procedure of Hatfield et al [20] [21] with modifications [22]. Briefly samples were buffer (50 mM TRIS pH 6.7), washed before incubated in a 90˚C water bath for 2 h followed with addition of amylase (Sigma A3403 10 U/tube) and amyloglucosidase (Fluka 10115 10 U/ tube).…”
Section: Preparation Of Tissue Materials For Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Ground samples were processed following the procedure of Hatfield et al [20] [21] with modifications [22]. Briefly samples were buffer (50 mM TRIS pH 6.7), washed before incubated in a 90˚C water bath for 2 h followed with addition of amylase (Sigma A3403 10 U/tube) and amyloglucosidase (Fluka 10115 10 U/ tube).…”
Section: Preparation Of Tissue Materials For Analysismentioning
confidence: 99%
“…Cell wall residues were dried in a 55˚C oven prior to hydrolysis [23] as modified by Hatfield [24], derivatization [25], and analyzed by FID-GLC (Supelco SPB-225 column 30 m × 0.25 mm with 0.25 micron film thickness). Total uronosyls were measured according to the methods described by Hatfield [22].…”
Section: Structural Analysis Of Leaf Sheath Stemmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross linking provided by lignin in grass secondary cell walls allows herbaceous panicoids to reach up to several meters in height. Leaf lignin content is highest in sheaths and midribs of the leaf blades making these more rigid to support a plant architecture that maximizes photosynthetic capacity [ 2 , 3 ]. The lignin constituent is particularly diverse, involving several possible linkages among the basic monolignol subunits [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The leaf sheath wraps around the stem in maize and is believed to provide strength for the growth and development of the leaf blade. Hatfield and colleagues compared changes in the cell wall component in maize leaf blades [15], midribs and sheaths from nodes 9 to 14 and concluded that sheath and midrib tissues always accumulate more neutral sugars, lignin and total phenolics than blade tissues. These metabolite measurements may explain the higher mechanical strength of leaf sheaths; however, information at the molecular level is still limited.…”
Section: Introductionmentioning
confidence: 99%